(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Even though Fintech is also transforming financial inclusion in Africa, its influence is not well studied. This systematic literature review studied the status quo of Fintech in Africa. Our study focused on the following factors: adoption affectors, opportunities Fintech provides, and the challenges documented to have been faced so far, based on academic literature. The study found that Fintech is playing a major role in the improvement of financial inclusion in the region, as it has created opportunities for the unbanked population. It has also provided easy access to remittances and reduced money crimes by providing secure ways of transferring money through mobile phones. The study, however, revealed that Africa still faces various challenges, such as poor financial infrastructures, financial illiteracy, lack of awareness, and poor internet connections in rural areas, among others. The study contributes to the existing body of knowledge on financial inclusion. It also offers insights on best practices to guide fintech players regarding areas to focus on to increase financial inclusion. It also guides scholars seeking other appropriate research fintech areas in Africa.